The importance of current megatrends and trends in the opinion of X and Z generations - Wicka, Aleksandra; Wicki, Ludwik (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
Contemporary changes in the world can be described by looking for similarities in phenomena occurring in different places. Currently, such megatrends include, among others: Demographic Shifts, Multipolarization of the World, Symbiocene, Bioera, and Mirror World. They are strongly related to technological progress, digitalization, and changes in societies. The aim of this article is to answer the question of whether the development trends are perceived as equally important by representatives of generations X and Z. Their attitude will be related to the willingness to accept the anticipated and already occurring changes. The research was conducted in 2023 on a sample of 500 people from generations X and Z. It was found that regardless of their generation, the respondents considered all megatrends current and important. They rated the importance of the Mirror World megatrend as the lowest, which means they are skeptical about the rapid domination of relationships by those taking place mainly on the Internet. The trends perceived as important included Mental Well-Being, Loneliness, Depopulation, and Roboticized Life, while the following were considered less important: Deglobalization, Medicine Resistance, Nation-State Collapse, and Identity Nomads. By comparing the assessments of trends by the representatives of the X and Z generations, it was found that the importance of each of the examined trends was assessed higher by younger people from Generation Z. For the most current trends, the differences in the assessments are statistically significant.
Keywords: trends; megatrends; generation X; generation Z; technological changes